Politik Hukum Pemenuhan Hak atas Kesehatan Pasca Penghapusan Ketentuan Mandatory Spending: Legal Policy of Fulfilling the Right to Health After the Erasure of Mandatory Spending Provisions - Nufitasari, Dien; Anam, Mohammad Choirul; Wiwoho, Jamal; Muryanto, Yudho Taruno; Wardhono, Dwi Tjahja Kusumo (SHARE Journal, 2025)
Law Number 17 of 2023 on Health has erased the requirement to allocate 5% to the health sector from the State Revenue and Expenditure Budget and 10% from the Regional Revenue and Expenditure Budget. It was previously required under Law Number 36 of 2009 concerning Health. This paper analyzes the fulfillment of the right to health following the removal of the mandatory spending provision. The authors employ legal methodology, adopting both normative and conceptual approaches. The study reveals that the government erased the mandatory spending norm for several reasons. Some of these stem from limited fiscal space and program flexibility, constrained by budget efficiency arising from the existence of the national health insurance, the emergence of new areas of corruption in the health sector, and the misallocation of the health budget. The legal policy of the Health Law should explicitly allocate 10%–20% to the health sector and include targeted, structured, and well-planned programs to achieve the greatest possible prosperity for the people. This allocation amount is comparable to expenditures in the education sector, underscoring that mandatory health spending reinforces the responsibility of both central and local governments to allocate sufficient health budgets as a national priority.